ECOLOGICAL AND HYGIENIC ASSESSMENT OF ATMOSPHERIC AIR IN THE OBSERVATION AREAS OF THE REGION - Ibodullayeva Sevara Saliybayevna; Ikramova Nargiza Alisher qizi; Maxmudova Margʻubaxon Fayziraxmon qizi (Modern American Journals, 2025)
Public health has always been and remains the primary criterion for the socioeconomic development of society, and its preservation and strengthening is one of the main priorities of state policy. The Basic Law of the Constitution, the Law "On the Sanitary and Epidemiological Welfare of the Population," stipulates that citizens have the right to a favorable living environment (the natural environment, working conditions, living, living, and recreational), factors that must not have a dangerous or harmful effect on the human body of present and future generations.